Mechanoregulation of YAP and TAZ in Cellular Homeostasis and Disease Progression - Cai, Xiaomin; Wang, Kuei-Chun; Meng, Zhipeng (Frontiers in Cell and Developmental Biology, 2021)
Biophysical cues, such as mechanical properties, play a critical role in tissue growth and homeostasis. During organ development and tissue injury repair, compressive and tensional forces generated by cell-extracellular matrix or cell-cell interaction are key factors for cell fate determination. In the vascular system, hemodynamic forces, shear stress, and cyclic stretch modulate vascular cell phenotypes and susceptibility to atherosclerosis. Despite that emerging efforts have been made to investigate how mechanotransduction is involved in tuning cell and tissue functions in various contexts, the regulatory mechanisms remain largely unknown. One of the challenges is to understand the signaling cascades that transmit mechanical cues from the plasma membrane to the cytoplasm and then to the nuclei to generate mechanoresponsive transcriptomes. YAP and its homolog TAZ, the Hippo pathway effectors, have been identified as key mechanotransducers that sense mechanical stimuli and relay the signals to control transcriptional programs for cell proliferation, differentiation, and transformation. However, the upstream mechanosensors for YAP/TAZ signaling and downstream transcriptome responses following YAP/TAZ activation or repression have not been well characterized. Moreover, the mechanoregulation of YAP/TAZ in literature is highly context-dependent. In this review, we summarize the biomechanical cues in the tissue microenvironment and provide an update on the roles of YAP/TAZ in mechanotransduction in various physiological and pathological conditions.